Acute transverse myelitis caused by Paragonimus infection: a case report and review of the literature - Wen, Zhiguo; Chen, Meiqiu; Xia, Cong; Sun, Yawei; Zhang, Yifan (Frontiers in Medicine, 2025)
Acute transverse myelitis (ATM) is a rare but severe neurological disorder that can be triggered by infections, autoimmune conditions, or other factors. While the association between parasitic infections and ATM is uncommon, Paragonimus infection can cause significant neurological damage, posing a diagnostic challenge. We report the case of a 65-year-old male patient who developed acute limb weakness, sensory loss, and fever following abdominal pain. Initial diagnostic tests were inconclusive; however, advanced imaging and metagenomic sequencing of cerebrospinal fluid ultimately confirmed an Paragonimus infection. After treatment with praziquantel, the patient successfully regained substantial motor function. This case highlights the need to consider parasitic infections in endemic areas and demonstrates the critical role of advanced diagnostic tools, such as metagenomic sequencing, in achieving timely diagnosis and treatment, ultimately improving the patient’s prognosis.